Argon laser treatment of central serous chorioretinopathy - Ting- Bing Fang (Guoji Yanke Zazhi, 2013)
AIM: To observe the efficacy of the argon laser photocoagulation treatment of central serous chorioretinopathy(CSC). METHODS: The treatment groups: 18 patients(18 eyes), argon laser photocoagulation and oral jolethin, vitamin B1, inosine and venoruton tablets. Control group: 18 patients(18 eyes), oral lecithin complex iodine, vitamin B1, inosine, venoruton tablets. Foveal thickness and neuroepithelial layer detachment range were measured by optical coherence tomography(OCT)before treatment, after 1 month and 3 months post-operation to compare the decline in value of foveal thickness and neuroepithelial layer detachment range of the two groups. RESULTS: After 1 month of treatment, the decline in value of the center foveal thickness: the value of treatment group was 256±72μm; the value of the control group was 82±57μm, and the difference of the two groups, P <0.05; the decline in value of neuroepithelial layer detachment range: the value of the treatment group was 3 548±168μm, the value of the control group was 1 520±143μm, And the difference of the two groups, P<0.05. After three months of treatment, the decline in value of the center foveal thickness: the value of treatment group was 383±75μm, the value of the control group was 312±67 μm, and the difference of the two groups, P<0.05; decline in value of neuroepithelial layer detachment range: the value of the treatment group was 4 908±172μm, the value of the control group was 4 211±153μm, and the difference of the two groups, P <0.05. The differences were statistically significant between the treatment and the control groups(two independent samples t-test). CONCLUSION:Argon laser photocoagulation treatment of CSC is an effective treatment method and can significantly shorten the course.